The party and other stories ebook The party: book 1. - Ruzzier, Sergio (Fox & Chick, 2018)
Fox and Chick don't always agree. But Fox and Chick are always friends. With sly humor and companionable warmth, Sergio Ruzzier deftly captures the adventures of these two seemingly opposite friends. The luminous watercolor images showcased in comic-book panel form will entice emerging readers, while the spare text and airiness of the images make this early chapter book accessible to a picture book audience as well.